2017
DOI: 10.1111/joor.12502
|View full text |Cite
|
Sign up to set email alerts
|

Taste‐related sensations in old age

Abstract: The sense of taste is important as it allows for assessment of nutritional value, safety and quality of foods as well as for food enjoyment and quality of life. Several factors are suggested to be associated with taste sensitivity, and higher prevalence of taste disorder has been reported among older adults. This review focused on the reported causes and correlates of taste decline in older adults, with the aim to consolidating existing evidence and identifying gaps and limitations. Using a scoping review meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
12
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 93 publications
(123 reference statements)
4
12
0
2
Order By: Relevance
“…The present data also confirm that taste recognition decreases with increasing age, in line with data present in the literature [35]. The physiological changes that occur in the taste buds are one of the main determinants of decreased taste sensitivity with increasing age [36]. Feng et al showed that the overall number of taste buds and the number of taste cells per taste bud decrease with age, especially in men aged between 74 and 85 years [37].…”
Section: Discussionsupporting
confidence: 91%
“…The present data also confirm that taste recognition decreases with increasing age, in line with data present in the literature [35]. The physiological changes that occur in the taste buds are one of the main determinants of decreased taste sensitivity with increasing age [36]. Feng et al showed that the overall number of taste buds and the number of taste cells per taste bud decrease with age, especially in men aged between 74 and 85 years [37].…”
Section: Discussionsupporting
confidence: 91%
“…Prior research indicates that taste thresholds of renal patients increase with age and this finding is also in agreement with results of studies on healthy subjects (Ciechanover et al 1980;Vreman et al 1980;Ng et al 2004;Ogawa et al 2017). Therefore, it is important to consider the fact that our dialysis and control groups were not demographically well matched, especially in terms of age.…”
Section: Discussionsupporting
confidence: 88%
“…Taste sense is related to chronic disease, medication use, smoking, alcohol consumption, and oral disorders, including dehydration of oral mucosa [12,13]. A recent study has shown that the preference and habituation for a specific beverage and food is associated with diet [14].…”
Section: Discussionmentioning
confidence: 99%